Uma abordagem em engenharia dirigida por modelos e computação em nuvem para suportar o teste de modelos SAAS de código aberto - RABELO FILHO, Gerson Lobato (2015)
Cloud Computing is a computational paradigm which came with the idea of cloud-based services, resources and functionalities offered by enterprises to end users through service delivery models. The main models are Infrastructure as a Service (IaaS), Platform as a Service (PaaS), and Software as a Service (SaaS). Offered services and resources are commonly tested by testing and maintenance teams with the purpose of detecting and eliminating present failures. In relation to SaaS models, the most common test types used are functional, performance, scalability, component-based and tenant-based ones. However, tests like reliability, availability, usability and acceptance ones, more oriented to users, are less performed. In the field of Model Driven Engineering (MDE), the tests in SaaS, PaaS and IaaS models are performed through approaches like transformation of models and generation of test cases according to test types, allowing services and resources being tested with great quality and efficiency. This dissertation shows an approach based on Model Driven Engineering to support generation of availability, reliability, usability (after user uses the open-source SaaS model and answer a questionnaire about his/her profile and about the model) and acceptance test cases for SaaS models with open source code (Open Software as a Service Open SaaS). A framework and metamodels are proposed to this end, besides quantitatives metrics with the purpose of analize these criteria for the proposed Open SaaS model.